Analysis of geomagnetic secular variation for the last 1.5 Ma recorded by volcanic rocks of the Trans Mexican Volcanic Belt: new data from Sierra de Chichinautzin, Mexico. Issue 1 (10th July 2019) - Rodríguez-Trejo, A; Alva-Valdivia, L M; Perrin, M; Hervé, G; López-Valdés, N
Summary: The great wealth of volcanism along the Trans Mexican Volcanic Belt (TMVB) and the need to improve the secular variation curve of the Earth magnetic field of the region is the aim of this research. 300 oriented cores from 33 sites and 21 individual cooling units were acquired from Sierra de Chichinautzin volcanic field (ChVF) and Sierra de Santa Catarina (SSC). Directional analysis and rock magnetic experiments were performed (e.g. thermal demagnetization, hysteresis loop, susceptibility vs temperature), achieving 21 new averaged palaeomagnetic directions. New results are consistent with the previous studies on the same cooling unit. We compiled all the palaeomagnetic studies performed on the ChVF, updating age and calculating an average direction per cooling unit and estimating an overall mean direction for the ChVF (Dec = 359.1°, Inc = 35.3°, N = 33, k = 21.6, α95 = 5.5°, Plat = 87.7° N, Plong = 227.4° E, K = 31.8, A95 = 4.5°). Afterwards, we compiled all the previous palaeomagnetic studies along the whole TMVB with age ranging from 0 to 1.5 Ma, and constrained the directional analyses by specific quality criteria such as well-defined age, number of samples and quality of kappa) on the cooling unit consistency. The mean direction and virtual geomagnetic pole (VGP) estimated for the TMVB, during the periods 0–40 ka and 0–1.5 Ma, are close to the geographic pole, supporting the validity of the geocentric axial dipole hypothesis. The directional results of this study also fit well with the predictions at Mexico City of the models SHA.DIF.14k and CALS10k2 calculated for the last 14 ka. The dispersion of the VGP's on the TMVB are also consistent with the expected values proposed by different models of palaeosecular variation. However, large gaps in the temporal record remain that should be filled by further palaeomagnetic studies.